Optimized formation control of multi-agent system using PSO algorithm - Ahmed M. Hasan; Safanah M. Raafat (Indonesian Journal of Electrical Engineering and Computer Science, 2020)
Formation Control (FC) is an important application for Multi-agent Systems (MASs) in coordinated control and especially for Unmanned Aerial Vehicle (UAV) which are widely used nowadays in military and civil sections. FC is mostly applied in conjunction with consensus algorithm. In this paper, a framework for an implementation of consensus FC that involves the decentralized type of network control is considered in order to achieve  formation keeping, where the control of each vehicle is calculated dependent upon locally existed facts. The dynamic behavior of each vehicle agent is governed by its second-order dynamic model, and the networked mobile vehicle system is modeled by a directed graph. Then, particle swarm optimization (PSO) is implemented for speeding up the convergence to the desired geometrical shape. Acceleration of the network while approaching the coveted shape is achieved and omissions of undesired swing that transpires through the acceleration is examined. The merits and effectiveness of the applied approach are demonstrated using two different examples.